Apartheid, clinical psychology, and breaking barriers - Pillay, Anthony L. (PINS-Psychology in Society, 2016)
Accepting an invitation to review the book Apartheid and the making of a Black psychologist was an easy decision despite competing demands and deadlines. It was, after all, a memoir by Chabani Manganyi. As a student, I had great admiration for Manganyi, because he represented hope for aspiring psychologists of colour in a country marked by fervent attempts to suppress Black advancement. My earliest recollection of this icon of South African Psychology relates to his book Being-black-in-the-world (1973), which not only got many hooked on his writing and urged a following of his work, but it provoked a critical engagement with issues of race and the social and political forces that affected the lives of the majority of South Africans. That he published the work at a time when not many were raising these issues in the literature earned him enormous respect.